Bridging Assessment Knowledge and Practice: Pre-Service EFL Teachers’ Assessment Literacy in Evaluating Pragmatic Competence - Entika Fani Prastikawati; Senowarsito; Dodi Mulyadi; Maria Yosephin Widarti Lestari (SALEE: Study of Applied Linguistics and English Education, 2026)
This study emerges from the recognition that language assessment literacy (LAL) is critical for designing assessments congruent with a communicative language teaching approach to EFL contexts, especially concerning pragmatic competence, an underrepresented area of classroom assessment. Based on the multidimensional LAL framework proposed by Glenn Fulcher, this study investigated pre-service EFL teachers' learning about language (LAL) during teaching practicum. Using an explanatory sequential mixed-methods design, 68 sixth semester pre-service teachers were involved. Overall, LAL was moderate (M = 2.89), with moderate scores in both task design (M = 2.81) and rubric development ability as well as confidence when creating these tasks associated with high perceived challenges to their implementation (M = 3.78). These qualitative results show that much pragmatic competence is evaluated indirectly, focusing more on vocabulary and grammar than appropriateness of content. These results reflect a gap between theory and practice. Therefore, the study points out that more professional-oriented and field-sensitive training is required to reinforce pragmatic assessment in EFL teacher education.